(untitled) (Damascus University Journal for the basic sciences, 2025)
A biostratigraphic study of Maastrichtian sediments was conducted using two groups of foraminifera and coccoliths in the Sarna and Ain al-Tineh sections, in the north of the coastal chain. 37 samples of Foraminifera and 21 samples of Coccoliths were studied in the two sections. Three biozones of foraminifera have been identified that characterize the Maastrichtian sediments in Sarna section: (Globotruncana falsostuartizone, Gansserinagansserizone, Abathomphalus mayaroensiszone) coinciding to the coccolithszone UC20 and corresponding to the period extending from the top of the lower Maastrichtian to the top of the upper Maastrichtian, and two zones in Ain al-Tineh section (Globotruncanafalsostuarti zoneGansserinagansseri zone) corresponding the age of top of lower Maastrichtian –lower part of upper Maastrectian. Biostratigraphic correlation gave the presence of two subzones of coccoliths, UC20d and UC20b, in Sarna, and one subzone UC20b in Ain al-Tineh. A sedimentary lacuna was observed in the Ain al-Tineh section related to the absence of the foraminifera zone (Abathomphalusmayaroensis) and the two subzones of Coccoliths UC20d and UC20c that characterize the sediments of the Upper Maastrichtian summit. The integrated biostratigraphic correlation process indicated the presence a diachronism in the occurrence of Miculamurus between the eastern and western parts of the Mediterranean.